Mathematical modeling of the transmission dynamics of Malaria - Kon, Cynthia Mui Lian (Universiti Malaysia Sarawak (UNIMAS), 2010)
This thesis focuses on the development of appropriate compartmental models to describe the transmission dynamics of malaria so that the spread of this disease and its impact on the population can be comprehended in a deeper level. Firstly, a basic model is constructed where we have a system of differential equations for both the human and mosquito population. The basic eproduction number, R0 is defined and the stability of disease-free equilibrium points when 0 <1 and instability when R0>1 are analysed using the Routh-Hurwitz criterion and Descartes rule.